All Days 2016
DOI: 10.2118/182799-ms
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Fracturing Fluid Development Challenges: A Comparison Between Seawater-Based and Freshwater-Based Fracturing Fluids Using Two Types of Guar Gum Polymers

Abstract: During the past several years (i.e., 2006 to 2014), the US transformed the development of shale oil and gas from slow and steady into a shale gas boom by combining two already existing technologies—multistage hydraulic fracturing and horizontal wells. This helped the US once again be energy-independent regarding natural gas supply (Charlez 2015). Inspired by such success, the Kingdom of Saudi Arabia and the Middle East region are meeting the increasing energy demand by following similar steps (Bartko et al. 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…[ 13 , 14 ]. At an early stage of hydraulic fracturing, polymer fluids such as guar gum [ 15 , 16 ] was used mostly as a thickening agent for the fracturing fluid [ 17 , 18 ]. Laboratory experiments have shown that traditional polymer-based fluids generate residue(s), which can damage the formation and reduce the pore conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 , 14 ]. At an early stage of hydraulic fracturing, polymer fluids such as guar gum [ 15 , 16 ] was used mostly as a thickening agent for the fracturing fluid [ 17 , 18 ]. Laboratory experiments have shown that traditional polymer-based fluids generate residue(s), which can damage the formation and reduce the pore conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Barium dissolved from the drilling mud remnants can be reprecipitated as Barite . In some cases, large amounts of strontium-bearing mineral precipitates can form due to the nature of the connate brines . This behavior is complex and often basin specific.…”
Section: Water Chemistry and Shale Reactivitymentioning
confidence: 99%
“…CMHPG guar derivative is preferred in the industry for its better hydration, slower degradation, and tolerance to a low pH environments. Figure 2 shows the generic structure of CMHPG ([ 22 , 23 , 24 , 25 ]).…”
Section: Introductionmentioning
confidence: 99%